Cambrian origin of the CYP27C1-mediated vitamin A1-to-A2 switch, a key mechanism of vertebrate sensory plasticity. Issue 7 (5th July 2017) - Morshedian, Ala; Toomey, Matthew B.; Pollock, Gabriel E.; Frederiksen, Rikard; Enright, Jennifer M.; McCormick, Stephen D.; Cornwall, M. Carter; Fain, Gordon L.; Corbo, Joseph C.
Abstract : The spectral composition of ambient light varies across both space and time. Many species of jawed vertebrates adapt to this variation by tuning the sensitivity of their photoreceptors via the expression of CYP27C1, an enzyme that converts vitamin A1 into vitamin A2, thereby shifting the ratio of vitamin A1 -based rhodopsin to red-shifted vitamin A2 -based porphyropsin in the eye. Here, we show that the sea lamprey ( Petromyzon marinus ), a jawless vertebrate that diverged from jawed vertebrates during the Cambrian period (approx. 500 Ma), dynamically shifts its photoreceptor spectral sensitivity via vitamin A1 -to-A2 chromophore exchange as it transitions between photically divergent aquatic habitats. We further show that this shift correlates with high-level expression of the lamprey orthologue of CYP27C1, specifically in the retinal pigment epithelium as in jawed vertebrates. Our results suggest that the CYP27C1-mediated vitamin A1 -to-A2 switch is an evolutionarily ancient mechanism of sensory plasticity that appeared not long after the origin of vertebrates.